ANALISIS PRAKTEK LAYANAN PDAM (PERUSAHAAN DAERAH AIR MINUM) TIRTA SIAK KOTA PEKANBARU SERTA DAMPAKNYA TERHADAP KEPUASAN PELANGGAN - Maya Puspita Larasati; Ahmad Tarmizi Yussa (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The study attempt to know the level of objective practice PDAM services (Regional Water Company) Tirta Siak the city of Pekanbaru and its impact on costumer satisfaction. The indicators of the quality of services to use covering reliability, responsiveness, competence, acces, courtesy, communication, credibility, security, understanding knowing the costumer, tangible. Type research located in office PDAM Tirta Siak the city of Pekanbaru this is survey descriptive, namely prioritise list interview as a means of data collection an data collected with this device then used as the main raw to analyze the condition empiris for obyektivitas the existence of a purpose research on location minutely. There are two gropus of the population and samples to research is employes, a total of 5 people and costumers, the number 5 costumers in this case is those who are subscription water in PDAM Tirta Siak City of Pekanbaru. Engineering sampling to use in setting individual is sampling purposive sample. Type and engineering collecting data which used consisting of, primery data collected by used technique interview and secondary data collected used technique observation. While analysis techniques used data is to have technique descriptive analysis. Based on technique this analysis reserachers judging and inferring that pledge of PDAM services (Regional Water Company) Tirta Siak this city of Pekanbaru and its impact on costumer satisfaction be at intervals good enough. Recommendations need to be considered especially with respect to improvement a quality of water that always muddy and colored the quality of pipes who has not be used in order to create customer satisfaction.